2014
DOI: 10.1590/s0036-46652014000400004
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated to Adherence to Different Treatment Schemes With Meglumine Antimoniate in a Clinical Trial for Cutaneous Leishmaniasis

Abstract: The favorable outcome of the treatment of a disease is influenced by the adherence to therapy. Our objective was to assess factors associated with adherence to treatment of patients included in a clinical trial of equivalence between the standard and alternative treatment schemes with meglumine antimoniate (MA) in the treatment of cutaneous leishmaniasis (CL), in the state of Rio de Janeiro. Between 2008 and 2011, 57 patients with CL were interviewed using a questionnaire to collect socioeconomic data. The fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
5
0
5
Order By: Relevance
“…Between 2001 and 2013, only 4% of 777 patients treated at INI were lost to follow-up 10 . Another study found a significant association between greater adherence to treatment and the use of 5 mg Sb v /kg/day MA treatments 43 . Other authors reported that an intermittent schedule (longer than the standard schedule) was associated with a lower frequency of discontinuation of treatment and loss to follow-up 21 .…”
Section: Discussionmentioning
confidence: 96%
“…Between 2001 and 2013, only 4% of 777 patients treated at INI were lost to follow-up 10 . Another study found a significant association between greater adherence to treatment and the use of 5 mg Sb v /kg/day MA treatments 43 . Other authors reported that an intermittent schedule (longer than the standard schedule) was associated with a lower frequency of discontinuation of treatment and loss to follow-up 21 .…”
Section: Discussionmentioning
confidence: 96%
“…In several studies, treatment with Sb V accelerated healing of CL lesions when used at 10-30 mg/kg/day IV or IM for 20-30 days, but the success rate ranges between 25 and 90% depending on the population and the strain of Leishmania, and even at the higher doses there are relapses [3,7]. Importantly, this prolonged high-dose treatment regimen is associated with severe adverse effects including cardiotoxicity (prolonged QTc interval, premature beats, tachycardia, fibrillation), pancreatitis, liver and kidney toxicities, malaise, myalgia, and anorexia [8,9]. Lastly, there are growing reports in India, Iran, and Peru of emerging resistance to antimonials in the field [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…En la práctica del ortodoncista lo que más se observa empíricamente durante un tratamiento de ortodoncia es que el éxito o fracaso de éste se puede asociar a la sumatoria de factores descritos anteriormente (16), con una proporción de deserción del tratamiento hasta del 21.4 % (4). Esta variabilidad hace que los pacientes presenten inconvenientes en mantener su tratamiento de manera apropiada; vale decir, cumplimiento de todas y cada una de las recomendaciones del clínico (15,(17)(18)(19).…”
Section: Introductionunclassified
“…Autores como Haynes y Sackett (1980) y Morinsky, Green y Levine (1986) propusieron diferentes cuestionarios, los cuales se utilizan con mayor frecuencia en la e-ISSN 2357-4607 / Vol.15, n°. 28 / enero-junio 2019 / Bogotá D.C., Colombia Universidad Cooperativa de Colombia Juliana Cano Restrepo, Cecilia María Martínez Delgado práctica clínica médica debido a su alta especificidad, sencillez y brevedad (23)(24)(25)18).…”
Section: Introductionunclassified
See 1 more Smart Citation